20 Firearm-related injuries in-hospital settings and in-hospital mortality. (9th June 2015) - Mills, Brianna; Simonetti, Joseph; Rowhani-Rahbar, Ali
Abstract : Statement of purpose: The proportion of injuries involving firearms varies from <1% of unintentional nonfatal injuries to 51% of suicides. Differences between firearm injuries treated in emergency department (ED) and inpatient settings are not well characterised. To ascertain how mortality varies by treatment setting and injury intent, we examined associations between patient characteristics, intent, and risk of death in ED and inpatient settings in a large sample of patients with firearm injuries. Methods/approach: We identified all firearm injuries in the National Trauma Data Bank, 2009–2012. Analyses were stratified by age group (0–17/18–64/65–89) and treatment setting (ED/inpatient). The 6-hour (ED) and 30-day (inpatient) discharge survival by injury intent were estimated using the Kaplan-Meier Method. Clustered multivariate Poisson regression models were used to calculate risk ratios (RR) of mortality in each setting. Results: Records of 67, 212 firearm injuries were analysed. ED patients were demographically similar to inpatients. Mortality rates in the ED were higher than in the inpatient setting across intent categories and age groups. Intent was strongly associated with mortality, with evidence of race modifying this association. In the ED setting, risk of mortality was higher with self-inflicted injuries (RR = 6.65; 95% confidence interval (CI): 4.52, 9.77), assault injuries (RR = 2.01; 95% CI: 1.34, 3.01), and undetermined intent injuries (RR = 4.45; 95% CI: 2.06, 9.61) compared to unintentional injuries. In the inpatient setting, risk of mortality was higher with self-inflicted injuries (RR = 8.28; 95% CI: 7.10, 9.67), assault injuries (RR = 2.02; 95% CI: 1.73, 2.36), and undetermined intent injuries (RR = 3.04; 95% CI: 2.42, 3.08) compared to unintentional injuries. Conclusions: Patterns of firearm injury intent differ between ED and inpatient settings. The risk of death in ED and inpatient settings is notably higher for intentional than unintentional injuries. Significance and contributions: Accounting for injury intent identifies subgroups at particular risk of firearm mortality in different treatment settings.